Challenges in biosecurity implementation and implications for antimicrobial use in Uganda’s poultry sector - Ayebare, Dreck; Moodley, Arshnee (International Livestock Research Institute, 2025)
This study is part of a two-phase research initiative conducted between 2022 and 2025 in Wakiso and Soroti districts, Uganda, examining antimicrobial use (AMU), antimicrobial resistance (AMR), and farm management practices in smallholder poultry systems. The overall study objective was to generate evidence to inform policy and support practical, on-farm interventions to reduce unnecessary antimicrobial use. The longitudinal phase presented here was initiated in response to persistent high levels of routine AMU identified during the first phase. Using a longitudinal observational design, semi-intensive broiler flocks were followed across the full production cycle to examine patterns of antimicrobial use alongside biosecurity practices and vaccine performance under real-world farm conditions. Data were collected through repeated farm visits, structured treatment and cost records, and standardized biosecurity assessments. This enabled a detailed, production-stage specific analysis of AMU and its underlying structural drivers, generating actionable insights for antimicrobial stewardship in Uganda’s rapidly expanding poultry sector.